2009
DOI: 10.1002/hyp.7367
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Southern Oscillation link to the Blue Nile River Basin hydrology

Abstract: Abstract:The objective of this study is to evaluate the relationships of El Niño Southern Oscillation (ENSO) indices and the Blue Nile River Basin hydrology using a new approach that tracks cumulative ENSO indices. The results of this study can be applied for water resources management decision making to mitigate drought or flood impacts with a lead time of at least few months. ENSO tracking and forecasting is relatively easier than predicting hydrology. ENSO teleconnections to the Blue Nile River Basin hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 22 publications
8
46
0
Order By: Relevance
“…The GPCP data show a strong signal of increased (decreased) rainfall during La Niña (El Niño) years over the Sahel region up to about 18 • N, including the upper catchment of the Nile River. This result agrees qualitatively with previous observational analyses, which suggested that La Niña years are associated with above normal rainfall and El Niño years with below normal rainfall in the upper catchment of the Blue Nile (Eltahir, 1996;Wang and Eltahir, 1999;Amarasekera et al, 1997;De Putter et al, 1998;Camberlin et al, 2001;Abtew et al, 2009). Figure 8 shows the corresponding fields averaged over the nine-member ensemble of Reg-TB simulations.…”
Section: Difference Between La Niña and El Niño Yearssupporting
confidence: 89%
“…The GPCP data show a strong signal of increased (decreased) rainfall during La Niña (El Niño) years over the Sahel region up to about 18 • N, including the upper catchment of the Nile River. This result agrees qualitatively with previous observational analyses, which suggested that La Niña years are associated with above normal rainfall and El Niño years with below normal rainfall in the upper catchment of the Blue Nile (Eltahir, 1996;Wang and Eltahir, 1999;Amarasekera et al, 1997;De Putter et al, 1998;Camberlin et al, 2001;Abtew et al, 2009). Figure 8 shows the corresponding fields averaged over the nine-member ensemble of Reg-TB simulations.…”
Section: Difference Between La Niña and El Niño Yearssupporting
confidence: 89%
“…4, which shows the monthly discharge (JanuaryDecember) averaged over all El Niño (1965, 1968, 1969, 1972, 1982, 1983, 1986, 1987, 1991, 1992, 1995, 2002, and 2009), La Niña (1970, 1971, 1973, 1974, 1975, 1985, 1988, 1989, 2000, 2007, 2008, and 2010 and normal years (1966, 1967, 1976, 1977, 1978, 1979, 1980, 1981, 1984, 1990, 1993, 1994, 1996, 2001, 2003, 2005, 2006, 2011, and 2012). This confirms the results of previous studies that El Niño is mostly associated with below-average rainfall, and La Niña with above-average rainfall (Eltahir, 1996;Wang and Eltahir, 1999;Amarasekera et al, 1997;De Putter et al, 1998;Camberlin et al, 2001;Abtew et al, 2009). The JJAS discharge anomalies for the full analysis period are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4. Monthly discharge at Eldiem station averaged during El Niño (1965, 1968, 1969, 1972, 1982, 1983, 1986, 1987, 1991, 1992, 1995, 2002and 2009), La Niña (1970, 1971, 1973, 1974, 1975, 1985, 1988, 1989, 2000, 2007, 2008and 2010 and normal years (1966, 1967, 1976, 1977, 1978, 1979, 1980, 1981, 1984, 1990, 1993, 1994, 1996, 2001, 2003, 2005, 2006, 2011 and 2012). , the red line represents the threshold for the extreme flood/drought, and the dashed red line represents the threshold for drought/flood.…”
Section: Relation Of Pacific Sst and Discharge At Eldiem Stationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies investigated the teleconnections between the Ethiopian rainfall and the global sea surface temperature (SST) in order to find SST indices to use for Nile flow prediction (e.g., Eltahir, 1996;Abtew et al, 2009;Melesse et al, 2011). Eltahir (1996) showed that the SST anomalies over the tropical eastern Pacific Ocean explain 25 % of the interannual variability of Nile flow for the period 1872-1972.…”
Section: Introductionmentioning
confidence: 99%